2009
DOI: 10.1002/jrs.2404
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of single GaN nanowires by tip‐enhanced Raman spectroscopy

Abstract: Raman imaging of a single [110]GaN nanowire using a combination of an atomic force microscope (AFM) and an inverted confocal microscope was investigated. The Raman spectra and associated maps of this single object, the diameter of which was of 200 nm, were collected in both confocal mode and with the interaction of an AFM tip to benefit from local tip enhancement effect. Beyond the pure tip-enhanced Raman scattering (TERS) effect, the setup was developed to integrate a commercial AFM and spectrometer to permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 20 publications
0
29
0
1
Order By: Relevance
“…Marquestaut et al studied isolated GaN nanowires, and reported that the near-field enhancement factor depends on the symmetry of the specific vibrational mode [103]. Böhmler et al were able to image single CdSe nanowires using tip-enhanced Raman and PL spectroscopy, thus differentiating the PL energy emission of nanowires with different diameters [104].…”
Section: -D Materialsmentioning
confidence: 99%
“…Marquestaut et al studied isolated GaN nanowires, and reported that the near-field enhancement factor depends on the symmetry of the specific vibrational mode [103]. Böhmler et al were able to image single CdSe nanowires using tip-enhanced Raman and PL spectroscopy, thus differentiating the PL energy emission of nanowires with different diameters [104].…”
Section: -D Materialsmentioning
confidence: 99%
“…Moreover, further ideas have been recently proposed for the Raman study of single NWs or Nanotubes. 18,19 It has been shown that strong enhancement of the Raman scattering could occur depending on the NW diameter, excitation wavelength and incident polarization. 18 The increased sensitivity of this technique by Tip-Enhanced Raman Spectroscopy (TERS) has also been reported for single GaN NW.…”
Section: Introductionmentioning
confidence: 99%
“…18 The increased sensitivity of this technique by Tip-Enhanced Raman Spectroscopy (TERS) has also been reported for single GaN NW. 19 Even if near-field Raman scattering (surface-enhanced and tip-enhanced Raman scattering) are still challenging techniques for semiconducting nanostructures studies, recent advances exploiting plasmonic effects are promising in view of the careful analysis of narrowest single NWs on specific substrates. 20,21 Here, we report on the UV μ-Raman spectroscopy of a single GaN/AlN NW grown by Molecular Beam Epitaxy (MBE).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, TER spectra of semiconductor materials, such as SiC surfaces [55] or GaN nanowires, [56] and the TER response of graphene of varying thickness have been studied with nanometer spatial resolution, [55,57] extending the application of TERS toward inorganic substrates with exciting physico-chemical properties.…”
Section: Materials Sciencementioning
confidence: 99%